Renal toxicological evaluations of sulphonated nanocellulose from Khaya sengalensis seed in Wistar rats. (25th March 2018) - Adewuyi, Adewale; Otuechere, Chiagoziem A.; Adebayo, Olusegun L.; Anazodo, Chibuzo; Pereira, Fabiano V.
Abstract: Nanocellulose is currently gaining attention due to its unique properties. This attention includes its application as building blocks for developing novel functional materials, plant drug and also in drug delivery systems. However, its safety remains largely untested or less understood. Thus, sulphonated nanocellulose (KSS) was prepared from cellulose (KSC) isolated from Khaya senegalensis seed (KS). KS, KSC and KSS were characterized using Fourier transformed infrared (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TG), particle size distribution (PSD), zeta potential and scanning electron microscopy (SEM). The impact of KSS on selected renal markers of oxidative stress, inflammation and apoptosis in Wistar rats was also investigated. Thus, male rats were randomly assigned to four groups of five animals each and were treated with KSS (0, 50, 75 and 100 mg/kg BW) for 14 days. Thereafter, biomarkers of renal oxidative damage, inflammation and immunohistochemical expressions of iNOS, COX-2, Bcl-2 and p53 were evaluated. The results revealed KSS to have crystallinity of 70.40%, it was monomodal and has a flaky surface with agglomerations. KSS had no effect on markers of kidney function and oxidative damage, although there was a generalized hypernatremia after 14 days of exposure. Lastly, KSS enhanced the antioxidant status and immunohistochemical expressions of iNOS and COX-2 in the kidney of the rats. While the biomedical applications of KSS may appear plausible, our data suggests that it could induce renal toxicity via the combined impacts of electrolyte imbalance and inflammation. Graphical abstract: Highlights: KSS was prepared from Khaya senegalensis seed for the first time. Khaya senegalensis seed was found to be a good source of nanocellulose. KSS enhanced the antioxidant status of the fed rats. KSS caused moderate cortical congestion. KSS enhanced the immunohistochemical expressions of iNOS and COX-2.